População em situação de rua no Brasil: o processo de intervenção estatal e suas especificidades no neoliberalismo - Rocha, Giuliana Barbosa da (2021)
The present study presents an analysis of the homeless population in Brazil and the responses of the Neoliberal State to this phenomenon. We sought to discuss the socio-historical aspects related to the urbanization process and the formation of the homeless population in Brazil; to verify how, in the course of capitalist development in Brazil, the State has behaved in the face of actions directed at the homeless population in Brazil; and to identify the answers offered by the Brazilian State in dealing with questions aimed at the homeless population through the state of counter-reform of the State. The proposed research problem is reflected in the following question: how in the face of the advancement of the Neoliberal project in Brazil, the homeless population has been treated by the State, given that this population has always received specific actions of an emergency nature and without continuity? To deal with the proposed theme, the methodological path of the research proceeded with a bibliographic survey for literature review and construction of the theoretical foundation. The research design is quantitative and qualitative and is characterized as bibliographic research. And to meet methodological and chronological criteria about the national dynamics of more evident approaches with Neoliberalism in Brazil, the period 1990 - 2020 was adopted as a period of research for the subsidies of specific State policies for the population in situation in the country. The main result found is that the main answers offered by the Brazilian neoliberal state in dealing with questions aimed at homeless people are based on two opposite, Liberal Social State and Penal State, which develop actions. The first in the perspective of social protection in a focused and superficial way. While the second used the power of coercion.